KERIS DALAM TRADISI SANTRI DAN ABANGAN - Rohman, Fatkur; Laili, Rifchatul (IAIN Tulungagung, 2018)
Keris for Javanese people is a cultural identity that cannot be separated from all Javanese cultural activities. The phenomenon of keris ownership is often misunderstood by some Javanese themselves. This is due to a perception that Keris is related to mysticism which is understood by some Javanese closely to abangan group. This anxiety creates a question: is there any relationship between keris ownership and Javanese religious variants? mainly abangan and santri, especially how santri interprets keris ownership. In this research, the methodology used is the anthropology and kerisology approach. The data are collected by conducting in-depth interviews. In practice, the keris is a complementary attribute of all traditions that are bound by mysticism (magic) for Javanese people. This is also evident in the ownership of the keris in the tradition of two variants of Javanese religion, abangan and santri. In fact, the ownership of the keris was not only for the abangan, but also among the santris. Apart from the inherent negative perception, the keris is actually one of Javanese cultural identities and heritage that needs to be saved and preserved. Keywords: Abangan, Keris, Mystic, Santri. Keris bagi orang Jawa merupakan identitas budaya yang tidak bisa lepas dari segala aktifitas kebudayaan Jawa. Fenomena kepemilikan keris sering disalahpahami oleh sebagian masyarakat Jawa sendiri. Hal ini didasarkan pada keris identik dengan mistik yang dipahami oleh sebagian masyarakat Jawa melekat erat dengan abangan. Berangkat dari kegelisahan tersebut, adakah hubungan kepemilikan keris dengan varian agama Jawa utamanya abangan dan santri, terutama bagaimana santri memaknai kepemilikan keris. Dalam penelitian ini, metodelogi yang digunakan adalah pendekatan antropologi dan kerisologi. Pengumpulan data dengan melakukan interview mendalam. Adapun pada praktiknya, keris merepukan atribut pelengkap segala tradisi (lakon) yang terikat dengan mistik (magic) bagi masyarakat Jawa. Hal ini juga tampak pada kepemilikan keris dalam tradisi dua varian agama Jawa, abangan dan santri. Kenyataannya, kepemilikan keris tidak hanya bagi kalangan abangan, dalam kalangan santri pun memiliki tradisi kepemilikan keris tersebut. Terlepas dari ?konotasi? negatif yang melekat, keris sesungguhnya merupakan salah satu identitas dan warisan budaya Jawa yang perlu dijaga dan dilestarikan. Kata kunci: Abangan, Keris, Mistik, Santri.